Penerapan Pendekatan Kontruktivis Dalam Pembelajaran Untuk Meningkatkan Hasil Belajar Struktur Aljabar Mahasiswa di Program Studi Pendidikan Matematika PMIPAFKIPUNRI (Jurnal Pilar Sains, 2008)
Evaluation has a very strategic position in teaching position in teaching process. Thus, there is no effort canimprove the quality of teaching without any steps of evaluation, that is recently called teaching reflection.Activities that construct the knowledge learned is an activity must be done, because this activity gives abetter control than teaching which is waiting the explanation question angd gives responds. The studentsprefer writing to asking. To improve such the condition, the writer did do an action research in teaching thestructure of algebra by applying the approach of construction in teaching processs by the students asevaluation implementers. There are circles of teaching done in this research, circle A and circle B. Both ofthem applied the constructive approach. The different is that action in circle B is an action of perfecting incircle A based on the evaluation by the students. The result of this evaluation toward the teaching is calledrespond. There are two ways in collecting the data, essay test and open observation test in order to answer theproblem. The data analyzed bybusing description, narration, table and diagram. Finally, the writer gives someconclusions. The first, there are positive influence felt by the students as long as they used that teachingprocess, the increasing of confidence, active-ness, interaction and self-confident to give responds. Thesecond, there are some problem faced by students during teaching process, such as, lack of confidence, lackof material mastering, material in English, laziness to discuss before class, bad responsibility in some groups,timing problem. In additional, some of the members of other groups complicate others students. The third,suggestions given by the students are using material in Indonesia, making Students Activities Papers (LKM)as guidance to increase the counseling of the lectures. In this case, the subjects are reguired to have positevethinking toward other students in giving responds or questions. In additional, they also construct goodassociation and activeness and manage their time well.Key word: evaluation, contraction, and circle learning result.